Changes in Treg and Breg cells in a healthy pediatric population - Yiyi Luo; Yiyi Luo; Yiyi Luo; Daniel Acevedo; Daniel Acevedo; Daniel Acevedo; Alexandru Vlagea; Alexandru Vlagea; Anna Codina; Ana García-García; Ana García-García; Ana García-García; et al. (Frontiers in Immunology, 2023)
The interpretation of clinical diagnostic results in suspected inborn errors of immunity, including Tregopathies, is hampered by the lack of age-stratified reference values for regulatory T cells (Treg) in the pediatric population and a consensus on which Treg immunophenotype to use. Regulatory B cells (Breg) are an important component of the regulatory system that have been poorly studied in the pediatric population. We analyzed (1) the correlation between the three immunophenotypic definitions of Treg (CD4+CD25hiCD127low, CD4+CD25hiCD127lowFoxP3+, CD4+CD25hiFoxP3+), and with CD4+CD25hi and (2) the changes in Treg and Breg frequencies and their maturation status with age. We performed peripheral blood immunophenotyping of Treg and Breg (CD19+CD24hiCD38hi) by flow cytometry in 55 healthy pediatric controls. We observed that Treg numbers varied depending on the definition used, and the frequency ranged between 3.3–9.7% for CD4+CD25hiCD127low, 0.07-1.6% for CD4+CD25hiCD127lowFoxP3+, and 0.24-2.83% for CD4+CD25hiFoxP3+. The correlation between the three definitions of Treg was positive for most age ranges, especially between the two intracellular panels and with CD4+CD25hi vs CD4+CD25hiCD127low. Treg and Breg frequencies tended to decline after 7 and 3 years onwards, respectively. Treg’s maturation status increased with age, with a decline of naïve Treg and an increase in memory/effector Treg from age 7 onwards. Memory Breg increased progressively from age 3 onwards. In conclusion, the number of Treg frequencies spans a wide range depending on the immunophenotypic definition used despite a good level of correlation exists between them. The decline in numbers and maturation process with age occurs earlier in Breg than in Treg.